Traditional Chinese medicine lowering lipid levels and cardiovascular events across baseline lipid levels among coronary heart disease: a meta-analysis of randomized controlled trials - Xie, Lihua; Liu, Jia; Wang, Xiaochi; Liu, Birong; Li, Jiaqi; Li, Jingen; Wu, Huanlin (Frontiers in Cardiovascular Medicine, 2024)
Background Dyslipidemia is a critical driver in the development of coronary heart disease (CHD), which further exacerbates the risk of major adverse cardiovascular events (MACEs). Chinese herbal medicine (CHM) plays an important role in the regulation of lipid levels and improvement of prognosis. However, few systematic reviews report whether the efficacy of CHM therapy for regulating lipid levels and lowering cardiovascular events is associated with baseline lipid levels. Methods Randomized controlled trials assessing efficacy of CHM for lipid profiles and MACEs among patients with CHD were searched in six databases. Two authors independently extracted studies according to a predesigned form. Cochrane risk of bias tool and Grading of Recommendations Assessment, Development, and Evaluation system were used to assess the methodological quality of the included studies. The primary outcomes were blood lipid levels and MACEs including cardiovascular mortality, non-fatal myocardial infarction, revascularization, angina pectoris, heart failure, and non-fatal stroke across baseline lipid levels. The secondary outcomes were individual components of the primary outcomes. Results A total of 23 trials with 7,316 participants were included in this study. Altogether 377 cardiovascular events occurred in 3,670 patients in the CHM group, while 717 events occurred in 3,646 patients in the Western medicine–alone group. Compared with the Western medicine alone, additional CHM significantly lowered low-density lipoprotein cholesterol (LDL-C) [MD = −0.46, 95% CI (−0.60 to −0.32), P < 0.00001, I2 = 96%]. The risk reduction in MACEs associated with CHM vs. Western medicine therapy was 0.52 [95% CI (0.47–0.58), P < 0.00001, I2 = 0%], but varied by baseline LDL-C level (P = 0.03 for interaction). Triglycerides (TG) level was also significantly lowered by additional CHM vs. Western medicine alone [MD = −0.27, 95% CI (−0.34 to −0.20), P < 0.00001, I2 = 81%], and risk reduction for MACEs also varied with baseline TG, with greater risk reduction in higher baseline TG subgroups (P = 0.03 for interaction). Similar results were observed with total cholesterol and high-density lipoprotein cholesterol. Conclusion Compared with Western medicine alone, additional CHM was associated with lower risk of cardiovascular events and improvement of lipid profiles. Risk reduction for cardiovascular events was associated with baseline LDL-C and TG levels. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO, identifier CRD42023425791.